Relationship Between Learning Styles and Physics Learning Outcomes of Class X Science Students - Fatmawati, Fatmawati; Khaeruddin, Khaeruddin; Haris, Abdul; Palloan, Pariabti; Usman, Usman (Jurnal Pendidikan Fisika, 2022)
This study aims to describe the learning styles and physics learning outcomes of class X science students at MAN 1 Polewali Mandar and the relationship between the two variables. This research is a quantitative descriptive research employing survey design. Data collection were carried out by distributing online learning style questionnaires using google forms and giving cognitive tests in the form of multiple choice to 124 students. To help determine the influence of learning styles toward learning outcomes of physics, inferential analysis in the form of Pearson product moment correlation analysis was used. The results showed thatthe most of the students in class X science at MAN 1 Polewali Mandar had visual learning styles, and only few of them had kinesthetic learning styles and auditory learning styles. Some students were not categorized in one specific learning style as they are not dominant in any of the three.In addition, majority of the female students had a visual learning style, while majority of the male students had kinesthetic learning style. Furthermore, the students’ physics learning outcomes were in medium category. Finally, there was a weak relationship between learning styles and students' physics learning outcomes.